Autonomy and care -seeking in adolescent mental health - Olivari, Cecilia; Núñez, Rodrigo; Ferrufino-Borja, Daniela; Méndez-Bustos, Pablo (Acta Bioethica, 2025)
One of the main strategies for mental health prevention is timely access to professional help. However, different barriers make it difficult for adolescents and young people to receive early access to professional care. The aim of this article is to reflect on the role of autonomy in seeking mental health help in the adolescent population. The construct of autonomy is approached from a developmental psychology and bioethical perspective. Then, research evidence is presented and described that relates autonomy with mental health issues, with some constructs related to psychological adjustment, and with help-seeking behavior for mental health problems. Based on this evidence, implications and guidelines for mental health prevention are discussed.